Implementation of Fuzzy Logic in Temperature Control Systems for Baking Ovens - Andhika Rizky Maulana; Chika Hayya Sabillah; Muhammad Faiz Assariy; Daffa Zulqhisti; Rahadian Ilyasa Muhammad; Mutiara Ade Rosseta; Fairuz Kamilah Ihsan; Melati Afdizha; Cindy Novitasari; Azhar Nasywa Saputra; Mrr Lukie Trianawati (Batrisya Education, 2025)
To produce bread of the highest quality, it is essential to use the right type of bread oven, especiallygiven the rapid growth of the bread industry. This study investigates the use of fuzzy logic as an automatedmethod for controlling the baking oven temperature. By using fuzzy logic, it is expected that the oven canmaintain an ideal temperature, resulting in consistent bread quality that meets expected standards. Fuzzy controlsystems differ from conventional control systems, which tend to be rigid.The aim of this research is to develop a more efficient automated control system for regulating oventemperature to ensure consistent bread quality throughout the baking process. It is hoped that, with thisautomated control system, bread quality will not only improve but also enhance the production efficiency of thebaking industry as a whole. Additionally, this study considers the type of bread being baked as a factorinfluencing the quality of the final product. Initial trials show that the fuzzy logic design produces satisfactoryresults, with the ability to adjust rules as needed.